Resistance to IFRS 13 - initial insights - Pandya, Anuradha (My University, 2016)
This paper explores the logics of resistance to fair value accounting, which entails the motivations to resist, as well as the mechanisms of resistance. It applies an interpretive approach to investigate this, using data collected from interviews with a sample of South African accounting professionals. The study demonstrates that while fair value accounting is being applied in the financial statements of organisations from a legalistic perspective, the application is superficial and ceremonious due to an established culture of compliance, and the need for funding, which engenders a ‘tick the box’ approach. The superficiality of application is complimented with a range of motivations to resist IFRS 13, which stem from practical concerns as well as theoretical, to create for a resistant attitude to fair value accounting. This resistance has been evidenced in this study, to manifest in various mechanisms that can be employed to avoid fair value accounting. These mechanisms are indicative of decoupling since they involve gaps being created between the purpose of financial statements, and the financial statements prepared, without blatant disregard of fair value accounting principles. These findings have been used to formulate recommendations which may be useful for preparers of financial statements, auditors and standard setters alike. While the aim of the study is not to identify deficiencies of fair value accounting principles, the consequence of exploring logics of resistance to fair value accounting is that it highlights areas that require further assessment in order to achieve the objectives of standards.
A research report submitted in partial fulfilment of the degree of Masters of Commerce in Accounting 2016.
Keywords: Fair value--Accounting standards; Corporations--Accounting--Standards; International business enterprises--Accounting--Standards; International financial reporting standards